Analysis of the adductors and abductors' maximum isometric strength on the level of speed and agility in basketball players - Paulina KROLIKOWSKA; Piotr RODAK; Monika PAPLA; Wojciech GRZYB; Artur GOLAS (Baltic Journal of Health and Physical Activity, 2023)
Introduction: his study investigated the relationship between hip abductor strength (Abd), adductor strength (Add), straight accelerations and decelerations, and during changes of direction (COD 90°) performance in basketball players.